High-throughput microarray for antimicrobial susceptibility testing - Anand Srinivasan; Grace C. Lee; Nelson S. Torres; Kevin Hernandez; Steven D. Dallas; Jose Lopez-Ribot; Christopher R. Frei; Anand K. Ramasubramanian (Biotechnology Reports, 2017)
We describe the development of a novel, high-throughput, nano-scale microarray platform for antimicrobial susceptibility testing (AST). The platform allows to process 480 samples at 50 nL volume on a single chip, analyze by fluorescence read-out with an easy dunk-and-rinse step, and the ability to process multiple samples and chips simultaneously. We demonstrate the applicability of this chip for culturing community acquired methicillin resistant Staphylococcus aureus (CA-MRSA), and perform AST against clinical isolates of CA-MRSA. The chip platform holds promise for an impact in microbial biotechnology as an attractive high-throughput, lower sample volume and quicker alternative to conventional AST such as the traditional broth microdilution or the newer automated systems. Keywords: Antimicrobial susceptibility testing, High-throughput, Microarray